An annotated field guide to tropical eco-engineering - Noraini Mohd. Tamin; Roslan Hashim (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
This Annotated Field Guidebook will be useful to practicing geo-technical engineers, botanists, ecologists, landscape planners, eco-engineers and post-graduate students. It highlights practical eco-engineering for erosion and sediment control and field preparation and logistics. This book also contains divergent use of many words and expressions pertinent to the field of erosion and sedimentation, storm water pollution control, and channel and shore protection. Where applicable, pictures are provided to assist users in understanding various terms, materials or structures.